Interaksi Sosial Keagamaan Narapidana di Lembaga Pemasyarakatan Kelas IIA Pematang Siantar - Damanik, Dearmaida; Syahminan, Mhd.; Muary, Rholand (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to determine the social interaction of religious inmates in the class IIA Pematang Siantar penitentiary, and to find out about the religious life of the inmates in the institution. Qualitative methods were used to obtain data through observation, interviews, and documentation. Data analysis used data reduction techniques, data presentation, and conclusion drawing through source triangulation and technique triangulation. The results showed that the religious social interaction in the institution involved social activities, religious activities, religious studies, tolerance among religious communities, and mutual respect. The religious life of the inmates was also categorized as good, with positive interactions and good implementation of religious guidance. However, new inmates tend to have difficulty adapting to the regulations set by the prison officials, and even show resistance.